Dampak Literasi Keuangan dan Perilaku Keuangan terhadap Pengelolaan Keuangan Generasi Z di Kota Makassar - Stevani Sartika (Fakultas Ekonomi dan Bisnis, 2025)
This study aims to examine the influence of financial literacy and financial behavior on financial management among Generation Z in Makassar City. The method used in this study is a quantitative method with multiple linear regression analysis, and data collection was conducted using questionnaires. The results of this study indicate that there is a positive and significant influence from both financial literacy and financial behavior on financial management among Generation Z in Makassar City. These findings reaffirm the importance of financial education from an early age, especially for Generation Z who grow up in the digital era with easy access to financial products and services.